Haiti : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation discusses that driven by popular frustration with high levels of corruption and inequality, Haiti has been experiencing a protracted political crisis and prolonged civil unrest. The baseline scenario assumes some stabilization in the political situation by early 2020 but no major political or economic reforms. This would allow growth to recover only gradually and in the absence of sustained implementation of good policies and structural reforms, potential growth would remain low at about 1.4 percent over the medium term. Downside risks, both domestic and external, remain elevated. A prolongation of political instability, extreme natural disaster, drop in remittances, and/or a contraction in exports because of trade tensions would worsen the outlook, particularly given the absence of buffers and fragile social conditions. The challenge is to stabilize the macroeconomic situation in an unstable political context. The IMF Staff encourages the authorities to continue their efforts to contain the fiscal deficit and its monetary financing by the central bank. Improving domestic revenue collection and redirecting current spending would help create space for much needed social and capital expenditures. Together with steps to strengthen the central bank's autonomy and legal framework, this would help reduce fiscal dominance.